Bioaccumulation and Bioavailability of Copper and Zinc on Mineral-Enriched Mycelium of Grifola frondosa - Figlas, Norma Débora (2010)
Grifola frondosa is an edible and medicinal mushroom. The bioaccumulation and potential biovailability of Cu and Zn were studied to obtain mycelium with potential properties as a food dietary supplement. Mycelia grown in the presence of nonmycotoxic concentrations of 100 and 200 ppm of Cu or 25 and 50 ppm of Zn accumulated 200–322 ppm and 267–510 ppm of Cu or Zn, respectively. When these enriched metal mycelia were subjected in vitro to a simulated gastrointestinal digestion, the solubility in these digestive fluids was 642–669 ppm and 102–530 ppm, which represent 32–33% and 0.7–3.5% of the recommended daily intake (RDI) for Cu and Zn, respectively, in 1 g of mycelium. These results are discussed in relation to the RDI values exhibited by two commercial supplements, and arguments are given on the potential use of these mineral-enriched mycelia in capsules (in the case of Cu-enriched mycelia), in food preparations, and also as a component of cosmetic mixtures.